Quand un homme amoureux raconte en « je » - Tóth, Ágnes (Verbum – Analecta Neolatina, 2006)
The first-person narrator of Prévost abbé's Histoire d'une Grecque moderne tells the story of his relationship with a beautiful Greek woman. The relation starts with a dialogue realized in a seraglio and this type of reported communication will dominate the whole narration. Most of these dialogues take place as part of a persuasion process: the actors try to persuade each other, and on his turn, the narrator tries to persuade the reader. The letter - the written communication par excellence - substitutes the dialogue between the actors only once, at a crucial moment of the story. This situation emphasizes one of the central problems raised by the novel: the failure of self-expression and mutual understanding.